2023
DOI: 10.1029/2022jb025729
|View full text |Cite
|
Sign up to set email alerts
|

Fault Weakening During Short Seismic Slip Pulse Experiments: The Role of Pressurized Water and Implications for Induced Earthquakes in the Groningen Gas Field

Abstract: Fluid production from and injection into subsurface reservoirs can cause multiple (micro)seismic events near boreholes and in surrounding fracture networks, as well as causing creep or seismic slip events on pre-existing faults (Ellsworth, 2013). In the giant Groningen gas field (northeast Netherlands), induced seismic events have occurred since the 1990s, with the strongest occurring on 16 August 2012 with a magnitude of M W 3.6. Most events are interpreted to occur along the pre-existing, high-angle, normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(40 citation statements)
references
References 59 publications
5
34
1
Order By: Relevance
“…This is a crucial input parameter for the heat budget of mm-scale seismic slip events, and hence for constraining effects such as thermal pressurization or flash heating effects that may control dynamic slip weakening during seismic slip (cf. Hunfeld et al, 2021;Chen et al, 2023).…”
Section: Implications For Small-displacement Earthquakesmentioning
confidence: 99%
“…This is a crucial input parameter for the heat budget of mm-scale seismic slip events, and hence for constraining effects such as thermal pressurization or flash heating effects that may control dynamic slip weakening during seismic slip (cf. Hunfeld et al, 2021;Chen et al, 2023).…”
Section: Implications For Small-displacement Earthquakesmentioning
confidence: 99%
“…Over the last 50 years, fluid‐rock interaction studies explored the influence of fluids on faults' seismic behavior, mostly based on the structure and composition of the fault rocks obtained from nature or friction experiments (e.g., Brantut et al., 2011; Duan et al., 2016; Y. Wang et al., 2022; Williams et al., 2017). They found that, during the co‐seismic phase, frictional heating rapidly increases pore fluid pressure, thus generating thermal pressurization effect that promotes dynamic weakening of the fault (e.g., Aretusini et al., 2021; Chen et al., 2023; Chester et al., 1993; Ferri et al., 2010; Kuo et al., 2021; Sibson, 1973; Ujiie et al., 2011; Wibberley & Shimamoto, 2005). After an earthquake, the permeability near the fault zone overall increases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these fluid-assisted chemical reactions lead to more abundant strong mineral phases (quartz, feldspar, and carbonates, 64%-87%) than weak clays (12%-36%) within the fault core, which locally strengthen the fault and promote the occurrence of earthquakes on this creeping fault. pore fluid pressure, thus generating thermal pressurization effect that promotes dynamic weakening of the fault (e.g., Aretusini et al, 2021;Chen et al, 2023;Chester et al, 1993;Ferri et al, 2010;Kuo et al, 2021;Sibson, 1973;Ujiie et al, 2011;Wibberley & Shimamoto, 2005). After an earthquake, the permeability near the fault zone overall increases.…”
Section: Introductionmentioning
confidence: 99%
“…0.01-0.3) over a given slip weakening distance Dw (Di . They include flash heating and associated weakening at early stages of slip (Proctor et al, 2014;Yao et al, 2016a, b), frictional melting at grain contacts (Wang et al, 2023), thermal decomposition (De Paola et al, 2011), bulk thermo-mechanical pore fluid pressurization (TP mentioned above; Aretusini et al, 2021;Faulkner et al, 2011;Hunfeld et al, 2021;Togo et al, 2011), silica gel production and lubrication (Di Toro et al, 2004;Rowe et al, 2019), thermochemical pressurization (Brantut et al, 2010), thermally activated super-plasticity (Chen et al, 2021;De Paola et al, 2015), pore water phase transitions from the liquid to the gaseous or supercritical state (Chen et al, 2017;Ferri et al, 2010: Oohashi at al., 2011, and flash pressurization (combined flash heating and TP at asperity contacts; Chen et al, 2023;Yao et al, 2018). The activation of any of the above-mentioned weakening mechanisms is typically dependent on the amount of frictional heat generated, which is controlled by experimental conditions (e.g.…”
Section: Strain Localization Frictional Heating and Dynamic Weakening...mentioning
confidence: 99%
“…In recent years, thanks to the improvement of experimental setup and pressure vessel design, higher normal stresses (up to 25 MPa) and elevated pore fluid pressures can be applied to watersaturated gouges deformed at seismic slip rates, with limited loss of gouge materials while maintaining an (undrained) fluid pressure to simulate more realistic natural faulting conditions (e.g. Aretusini et al, 2021;Chen et al, 2023;Hunfeld et al, 2021;Kuo et al, 2021).…”
Section: Current Knowledge Of Fault Dynamics In Small-magnitude Earth...mentioning
confidence: 99%